Sociopsychological Tailoring to Address Colorectal Cancer Screening Disparities: A Randomized Controlled Trial - Jerant, Anthony (American Academy of Family Physicians, 2014)
PURPOSE: Interventions tailored to sociopsychological factors associated with health behaviors have promise for reducing colorectal cancer screening disparities, but limited research has assessed their impact in multiethnic populations. We examined whether an interactive multimedia computer program (IMCP) tailored to expanded health belief model sociopsychological factors could promote colorectal cancer screening in a multiethnic sample. METHODS: We undertook a randomized controlled trial, comparing an IMCP tailored to colorectal cancer screening self-efficacy, knowledge, barriers, readiness, test preference, and experiences with a nontailored informational program, both delivered before office visits. The primary outcome was record-documented colorectal cancer screening during a 12-month follow-up period. Secondary outcomes included postvisit sociopsychological factor status and discussion, as well as clinician recommendation of screening during office visits. We enrolled 1,164 patients stratified by ethnicity and language (49.3% non-Hispanic, 27.2% Hispanic/English, 23.4% Hispanic/Spanish) from 26 offices around 5 centers (Sacramento, California; Rochester and the Bronx, New York; Denver, Colorado; and San Antonio, Texas). RESULTS: Adjusting for ethnicity/language, study center, and the previsit value of the dependent variable, compared with control patients, the IMCP led to significantly greater colorectal cancer screening knowledge, self-efficacy, readiness, test preference specificity, discussion, and recommendation. During the followup period, 132 (23%) IMCP and 123 (22%) control patients received screening (adjusted difference = 0.5 percentage points, 95% CI −4.3 to 5.3). IMCP effects did not differ significantly by ethnicity/language. CONCLUSIONS: Sociopsychological factor tailoring was no more effective than nontailored information in encouraging colorectal cancer screening in a multiethnic sample, despite enhancing sociopsychological factors and visit behaviors associated with screening. The utility of sociopsychological tailoring in addressing screening disparities remains uncertain.